2015
DOI: 10.3897/zookeys.504.8049
|View full text |Cite
|
Sign up to set email alerts
|

Status of Exosphaeroma amplicauda (Stimpson, 1857), E. aphrodita (Boone, 1923) and description of three new species (Crustacea, Isopoda, Sphaeromatidae) from the north-eastern Pacific

Abstract: Exosphaeroma amplicauda (Stimpson, 1857) from the west coast of North America is reviewed and redescribed and revealed to be a group of closely related species. A neotype is designated and the species redescribed based on the neotype and topotypic specimens. Exosphaeroma amplicauda is known only from the coast of California, at Marin, Sonoma and San Mateo Counties. Exosphaeroma aphrodita (Boone, 1923), type locality La Jolla, California and previously considered nomen dubium is taken out of synonymy and re-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Along the Washington to California coast this species commonly co-occurs with Exosphaeroma inornata Dow, 1958. The latter is known from Puget Sound, Washington to central-southern Baja California Norte, Mexico (Wall et al 2015). When specimens are very small and/or subadults, not only do the species of Gnorimosphaeroma get readily confused, but sometimes they are misidentified as E. inornata if not the most careful attention is paid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Along the Washington to California coast this species commonly co-occurs with Exosphaeroma inornata Dow, 1958. The latter is known from Puget Sound, Washington to central-southern Baja California Norte, Mexico (Wall et al 2015). When specimens are very small and/or subadults, not only do the species of Gnorimosphaeroma get readily confused, but sometimes they are misidentified as E. inornata if not the most careful attention is paid.…”
Section: Discussionmentioning
confidence: 99%
“…10, 11). Our Exosphaeroma amplicauda (Wall et al 2015) review resulted in the recognition of five species with Alaska and Washington specimens recognized as distinct from the type locality (Central California), and distinct from those from the Southern California coast. It would not be surprising if future studies based on broader sampling revealed greater genetic diversity than what we observed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many sphaeromatideans, the anterior pleonites often are partly overlapped or concealed completely by the last pereonite (Jacobs, 1987; Wall et al, 2015). In addition, some pleonites may be overlapped by other pleonites (Bruce, 1986; Brusca et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Specimens are prepared for SEM as described in Wall et al (2015). Drawings were made with the aid of a camera lucida and illustrations were electronically “inked” with Affinity Designer, Serif Labs.…”
Section: Methodsmentioning
confidence: 99%